STUDI EKSPERIMENTAL PENGARUH SUBSTITUSI FABA TERHADAP KUAT TEKAN DAN DURABILITAS BETON - Alamsyah; Vilna Shavira; Marzylina, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Fly ash and bottom ash (FABA) are abundant by-products of coal combustion that often present significant waste management challenges. FABA contains pozzolanic properties, which have the potential to enhance concrete performance. This study evaluates the utilization of treated FABA as a partial cement replacement in concrete mixtures at varying proportions of 3%, 6%, 9%, and 12%, focusing on compressive strength, porosity, and chloride ion permeability. The Rapid Chloride Permeability Test (RCPT), conducted in accordance with ASTM C1202 standards, was used to assess the concrete's permeability. The results demonstrate that incorporating FABA into the concrete mix significantly improves the concrete's quality, particularly regarding resistance to chloride ion penetration and reduced porosity. The concrete containing 6% FABA performed best among the various mix proportions tested, achieving the lowest RCPT values and porosity.